Interpretation of Tenun Bulu and Upcycled Denim in Ready-to-Wear “Veerangana” Based on Circular Fashion - Nur Aini, Tika; Krisnawati, Maria (Universitas Negeri Semarang, 2025)
This study aims to explain the application of the circular fashion concepts in the ready-to-wear fashion collection “Veerangana” through the utilization of upcycled denim and tenun bulu textiles within a single aesthetic and functional design. The research background is grounded in the increasing volume of textile waste resulting from linear consumption patterns and the limited use of traditional textiles in contemporary fashion, thereby indicating the need for innovation that supports environmental sustainability and the preservation of local culture. The method applied is Research and Development (R&D) using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation, encompassing literature review, concept and moodboard development, as well as the prototyping and construction of the “Veerangana” fashion. Product feasibility was assessed through expert judgment by three fashion design experts using six indicators: design, sizing, aesthetics, sewing technique, performance, and uniqueness indicators. The assessment results show that the “Veerangana” ready-to-wear fashion falls into the “Highly Feasible” category, thus meeting visual, constructional, and functional feasibility standards, and has the potential to serve as a model of circular fashion implementation that contributes to reducing textile waste and strengthening the position of tenun bulu within the sustainable fashion industry.